2013
DOI: 10.18433/j3zs3q
|View full text |Cite
|
Sign up to set email alerts
|

Safranal Treatment Improves Hyperglycemia, Hyperlipidemia and Oxidative Stress in Streptozotocin-Induced Diabetic Rats

Abstract: -Purpose. Clinical research has confirmed the efficacy of several plant extracts in the modulation of oxidative stress associated with diabetes mellitus. Findings indicate that safranal has antioxidant properties. The aim of the present study was the evaluation of possible protective effects of safranal against oxidative damage in diabetic rats. Methods. In this study, the rats were divided into the following groups of 8 animals each: control, untreated diabetic, three safranal (0.25, 0.50, 0.75 mg/kg/day)-tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
65
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 43 publications
10
65
1
2
Order By: Relevance
“…It was found that safranal (0.25, 0.50, and 0.75 mg/kg/day, i.p. for 4 weeks) improved streptozotocin-induced diabetes and its complications by the modulation of oxidative stress markers [28]. Hazman and Ovali also reported that safranal reduced inflammation (TNF-α and IL-1β) but increased oxidative stress markers due to experimental type 2 diabetes mellitus both in the plasma and pancreas tissue [9].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It was found that safranal (0.25, 0.50, and 0.75 mg/kg/day, i.p. for 4 weeks) improved streptozotocin-induced diabetes and its complications by the modulation of oxidative stress markers [28]. Hazman and Ovali also reported that safranal reduced inflammation (TNF-α and IL-1β) but increased oxidative stress markers due to experimental type 2 diabetes mellitus both in the plasma and pancreas tissue [9].…”
Section: Discussionmentioning
confidence: 97%
“…Safranal possesses a wide range of properties such as being anti-oxidant [3,13], anti-inflammatory [9,14], antidiabetic [21,28], antiseizure [11,12,24], anxiolytic [6], anti-hypertensive [16], cytoprotective [4] and anti-carcinogenic [22]. In our previous research, safranal displayed obvious protective effects on brain injury induced by transient global cerebral ischemia in rats [10].…”
Section: Introductionmentioning
confidence: 99%
“…GPx activity was determined in serum samples by spectrophotometry at 340 nm using a commercially available kit (Pars Azmoon Co., Iran) The GPx activity was unit per milligram of protein. [35].…”
Section: Measurement Of the Serum Antioxidants Enzymesmentioning
confidence: 99%
“…Способностью ингибировать PTP1B обладает и ряд других природных соединений: полибромистый дифенилэфир, выделенный из экстракта морской губки Lamellodysidea herbacea [61], рутамарин (Rut) [62], сафранал [63], экстракт, полученный из расте-ния Annona squamosa [64]. Рутамарин стимулирует транслокацию ГЛЮТ-4 и инсулинзависимый захват Стимулирование поглощения глюкозы клетками [27,28] 4548-G05 Стимулирование поглощения глюкозы клетками, сни-жение уровня глюкозы в крови [29] 3-О-метил-хироинозитол (пинитол) Снижение уровня глюкозы, ОХ, ТГ, свободных ЖК и ФЛ в сыворотке, печени, почках, сердце и мозге [31,32] Соли ванадия Стимулирование глюкозо-индуцированной секреции инсулина β-клетками, увеличение поглощения глюко-зы клетками и их чувствительности к инсулину, сни-жение продукции глюкозы печенью [35] TLK16998 Повышение чувствительности тканей к инсулину, уве-личение захвата глюкозы клетками, снижение уровня глюкозы в крови [30] TLK19780 Усиление инсулинзависимого транспорта глюкозы в клетки, увеличение чувствительности клеток к инсу-лину и максимального ответа на инсулин [38] 6Cl-TGQ Быстрый и продолжительный захват глюкозы клетка-ми, снижение уровня глюкозы и инсулина в крови, улучшение нарушенной толерантности к глюкозе Примечание.…”
Section: активация и потенцирование инсулиновой сигна-лизации улучшеunclassified
“…Сафранал индуцирует лиганднезависимую активацию инсу-линового сигнального каскада в культивируемых миотрубочках C2C12, а также при длительном перо-ральном назначении улучшает толерантность к глю-козе у мышей линии KK-Ay с моделью СД2 [65]. В опытах in vivo обнаружены антигиперлипидемиче-ский, антиоксидантный и гипогликемический эф-фекты сафранала, которые могут быть полезны в терапии осложнений СД [63,66]. Много исследований посвящено изучению ан-тидиабетической активности экстракта растения Annona squamosa.…”
Section: активация и потенцирование инсулиновой сигна-лизации улучшеunclassified